Prognostic Value of EMT-Circulating Tumor Cells in Metastatic Breast Cancer Patients Undergoing High-Dose Chemotherapy with Autologous Hematopoietic Stem Cell Transplantation - Michal Mego, Hui Gao, Bang-Ning Lee, Evan N. Cohen, Sanda Tin, Antonio Giordano, Qiong Wu, Ping Liu, Yago Nieto, Richard E. Champlin, Gabriel N. Hortobagyi, Massimo Cristofanilli, Naoto T. Ueno, James M. Reuben (Journal of Cancer, 2012)
Background: Circulating tumor cells (CTCs) are an independent prognostic factor in metastatic breast cancer (MBC) patients treated by conventional dose chemotherapy. The aim of this study was to determine the role of CTCs and CTCs undergoing epithelial-mesenchymal transition (EMT) in metastatic breast cancer. We used the platform of high-dose chemotherapy (HDCT) and autologous hematopoietic stem cell transplantation (AHSCT) to study the CTCs and CTCs with EMT. Patients and methods: CTCs were enumerated in 21 MBC patients before apheresis and 1 month after AHSCT. CD34-depleted apheresis products were analyzed for CD326+ epithelial and Aldefluor+ cancer stem cells (CSC) by flow cytometry and were depleted of CD45+ cells and assessed for EMT-inducing transcription factors (EMT-TF) by quantitative RT-PCR. Results: Patients with ≥ 5 CTCs/7.5 mL of peripheral blood 1 month after AHSCT had shorter progression-free survival (PFS) (P=0.02) and overall survival (OS) (P=0.02). Patients with apheresis products containing high percentages of CD326+ epithelial cells or overexpressing EMT-TF had shorter PFS. In multivariate analysis, low percentage of CD326+ epithelial cells and response to HDCT with AHSCT were associated with longer PFS, whereas lower CTCs after AHSCT was associated with longer OS. High CTCs, 1 month after AHSCT correlated with shorter PFS and OS in MBC patients undergoing HDCT and AHSCT, while CTCs with EMT and CSCs phenotype in apheresis products are associated with relapse. Conclusion: Our data suggest that CTC and CTCs with EMT are prognostic in MBC patients undergoing HDCT followed by AHSCT.